Weitbrechtova retinakula kycelního kloubu - Bartonícek, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1990)
On the basis of his own cadaver studies and data presented in the literature (mainly those presented by Anseroff) the author describes synovial folds of the hip joint also called retinacula of Weitbrecht and deals with the significance of these folds for the blood supply of the proximal end of the femur. In total there are three retinacula of Weitbrecht in the hip joint. Retinaculum anterius passes along the anterior surface of the neck originating from linea intertrochanterica toward the femoral head. It has the shape of a flat fold which is quite often divided into more stripes. Sometimes it is missing. Retinaculum mediale sometimes called Amantini's fold passes from the lesser trochanter to fovea capitis femoris along the medial surface of the neck. In children it has the shape of a single strip, in adults it most often has the shape of an upside-down "T". Its occurrence is constant. This applies also to retinaculum lateral passing along the superior surface of the neck from the greater trochanter toward the head. This retinaculum has always the shape of a flat plate. Corresponding to the number and course of retinacula is also the classification of the so called neck arteries into three groups as presented by Tucker and Ogden. In the lateral retinaculum there pass also so called posterosuperior retinacular vessels, in the medial one the so called posteroinferior retinacular vessels. Both groups of vessels originating from a profundus a. circumflexae femoris medialis supply the femoral head. In the anterior retinaculum there pass vessels of the same name originating from r. transversus a. circumflexae femoris lateralis.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Ligaments, Articular; novorozenec; Infant, Newborn; kloubní ligamenta; dospělí; Adult; Hip Joint; Humans; lidé; kyčelní kloub